Synthesis and Properties of Alkoxy‐ and Alkenyl‐Substituted Peralkylated Imidazolium Ionic Liquids. Issue 15 (23rd September 2013) - Maton, Cedric; Brooks, Neil R.; Van Meervelt, Luc; Binnemans, Koen; Schaltin, Stijn; Fransaer, Jan; Stevens, Christian V.
Abstract Novel peralkylated imidazolium ionic liquids bearing alkoxy and/or alkenyl side chains have been synthesized and studied. Different synthetic routes towards the imidazoles and the ionic liquids comprising bromide, iodide, methanesulfonate, bis(trifluoromethylsulfonyl)imide ([NTf2]−), and dicyanamide {[N(CN)2]−} as the anion were evaluated, and this led to a library of analogues, for which the melting points, viscosities, and electrochemical windows were determined. Incorporation of alkenyl moieties hindered solidification, except for cations with high symmetry. The alkoxy‐derivatized ionic liquids are often crystalline; however, room‐temperature ionic liquids (RTILs) were obtained with the weakly coordinating anions [NTf2]− and [N(CN)2]−. For the viscosities of the peralkylated RTILs, an opposite trend was found, that is, the alkoxy derivatives are less viscous than their alkenyl‐substituted analogues. Of the crystalline compounds, X‐ray diffraction data were recorded and related to their molecular properties. Upon alkoxy substitution, the electrochemical cathodic limit potential was found to be more positive, whereas the complete electrochemical window of the alkenyl‐substituted imidazolium salts was shifted to somewhat more positive potentials.